2010
DOI: 10.1093/toxsci/kfq040
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis in Cultured Neurons Is Altered by Chronic Alcohol Exposure

Abstract: Endocytosis is required for many cellular pivotal processes, including membrane recycling, nutrient uptake, and signal transduction. This complex process is particularly relevant in polarized cells, such as neurons. Previous studies have demonstrated that alcohol alters intracellular traffic, including endocytosis, in several cell types. However, information on the effect of chronic alcohol exposure on this process in neurons is scarce. As an approach, we investigated the effect of alcohol exposure on the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 68 publications
2
34
0
Order By: Relevance
“…Downstream, important effectors for active Rac1 and Cdc42 are the p21-activated kinases (PAKs), and for RhoA is Rho-kinase/ROCK. Previous studies from our laboratory and others confirm that ethanol alters the activity of Rho-GTPases and its effectors in neuronal cells [53] and non-neuronal cells [124,125,126], and regulates microtubules and F-actin cytoskeleton dynamics [127,128,129]. Using primary CGN culture from ethanol exposed seven-day-old pups, our laboratory found that moderate ethanol exposure (blood alcohol concentration 40 mM) inhibits the activation of RacI and stunts the formation of neurites, while RhoA activation at high dose of ethanol (blood alcohol 80 mM) promotes apoptosis [53].…”
Section: Ethanol Impairs Rhoa Gtpase Signalingmentioning
confidence: 93%
“…Downstream, important effectors for active Rac1 and Cdc42 are the p21-activated kinases (PAKs), and for RhoA is Rho-kinase/ROCK. Previous studies from our laboratory and others confirm that ethanol alters the activity of Rho-GTPases and its effectors in neuronal cells [53] and non-neuronal cells [124,125,126], and regulates microtubules and F-actin cytoskeleton dynamics [127,128,129]. Using primary CGN culture from ethanol exposed seven-day-old pups, our laboratory found that moderate ethanol exposure (blood alcohol concentration 40 mM) inhibits the activation of RacI and stunts the formation of neurites, while RhoA activation at high dose of ethanol (blood alcohol 80 mM) promotes apoptosis [53].…”
Section: Ethanol Impairs Rhoa Gtpase Signalingmentioning
confidence: 93%
“…In addition to RhoGTPases RhoA, Rac1 and Cdc42, these proteins include clathrin, adaptor AP-2, sorting nexin SNX9, GTPases Rab5, Rab11, or endosomal marker EEA1. In addition, ethanol exposure also affects the cholesterol cellular levels related with clathrin-independent endocytosis [17]. A toxic effect of alcohol on endocytosis can affect some important neuronal activities that depend on the endocytic process, including synaptic vesicle recycling, regulation of the number of signaling receptors, trafficking of postsynaptic receptors, polarized axon elongation, growth cone navigation, neuronal migration and hippocampal plasticity.…”
Section: Alcohol Affects Glycosylation and Intracellular Trafficking mentioning
confidence: 99%
“…For example, neuronal death has been reported in the cerebellum (Pickering et al, 2010), but not in the hippocampus (e.g. Marín et al, 2010).…”
Section: Discussionmentioning
confidence: 99%